Membangun MEMBANGUN KELAS SEJARAH INTERAKTIF DENGAN BANTUAN TEKNOLOGI DIGITAL: INOVASI DAN TANTANGAN - Titik Larasati (Jurnal Tunas Pendidikan, 2025)
In the study of history in Indonesian, the use of digital technology has enhanced students’ engagement and their understanding of historical material. This study was conducted at SMA Negeri 1 Tanjung Jabung Timur using a qualitative approach. The observation method was employed to observe how students interacted with interactive media such as animated videos, interactive maps, and web-based learning modules. The results showed that students were more engagement in class discussions and better understood more complex historical concepts. Digital technology has great potential to transform the paradigm of history learning into something more dynamic and relevant. This is despite issues such as the digital divide and the need for additional training for teachers. Indonesian can continue to move towards a more modern and inclusive future with a commitment to addressing these challenges.